Conservation and Utilization Strategy on Biodiversity of Indonesian Medicinal Plants - Ervizal Amir M Zuhud (Media Konservasi, 1989)
The biological natural resources in Indonesia is very abundant and varied. Among these resource, + 1000 species has been known and utilized as raw materials for medicine and traditionalbiomedicine Uamu). Generally, the medicinal and traditional biomedicine plants are procured directly from their natural habitat, without accompanied by planting activities. If this phenomena occurs continously, it will threatens the continued existence of medicinal plants diversity resources. The strategy of conservation and utilization of biodiversity of Indonesian medicinal plants has five main targets, namely : (1) conservation of genetic resource diversity of medicinal and traditional bio-medicine plants, (2) supplying raw materials for medicine and traditional bio-medicine by breeding and cultivation, (3) research and development of raw materials potential with has not been known, (4) development and creation of medicine and "jamu" industries, together with extension to people and (5) low and government regulation.